2019
DOI: 10.3390/nano9081131
|View full text |Cite|
|
Sign up to set email alerts
|

Interaction of Gold Nanorods with Human Dermal Fibroblasts: Cytotoxicity, Cellular Uptake, and Wound Healing

Abstract: Herein, the cytotoxicity, cellular uptake and wound healing of human dermal fibroblasts were investigated upon treatment with gold nanorods (GNR) decorated with different ligands. Neutral and cationic poly ethylene glycol (PEG)-decorated GNR demonstrated the least cytotoxicity and cellular internalization, while anionic- and bovine serum albumin (BSA)-coated GNR revealed significant cytotoxicity and cellular uptake into human dermal fibroblasts. The cell scratch test demonstrated that neutral, cationic PEGylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…The findings (Fig. 8) indicated that the Gold@-DEX/SS nanomaterials management facilitated substantial healing via fibroblast migration and adequate epithelial cell growth, as well as blood flow restoration via training of blood vessels [67][68][69][70]. To the best of our knowledge, in our attempt to create a new tissue treatment system, we established a Gold@DEX/SS dressing with DEX/SS encapsulated with Gold that was tested for the first time for its use in tissue implantation management.…”
Section: Antibacterial Properties and Cell Viability Analyses Of Dex/ss And Gold@dex/ssmentioning
confidence: 99%
“…The findings (Fig. 8) indicated that the Gold@-DEX/SS nanomaterials management facilitated substantial healing via fibroblast migration and adequate epithelial cell growth, as well as blood flow restoration via training of blood vessels [67][68][69][70]. To the best of our knowledge, in our attempt to create a new tissue treatment system, we established a Gold@DEX/SS dressing with DEX/SS encapsulated with Gold that was tested for the first time for its use in tissue implantation management.…”
Section: Antibacterial Properties and Cell Viability Analyses Of Dex/ss And Gold@dex/ssmentioning
confidence: 99%
“…Lysotracker CIS-PT-NPs with Dil (Molecular Probe, USA) stained the cell lysosome (red color), then DAPI stained the nuclei. Images were examined by confocal laser scanning microscopy (CLSM) utilizing the image analyzer software manufacturer's protocol [35][36][37].…”
Section: Cellular Uptakementioning
confidence: 99%
“…After 4-hour incubation, the cell number of each well was counted and then the cells were digested by aqua regia solution for 4 hours. [30][31][32][33]…”
Section: In Vitro Cytotoxicity Test and Cellular Uptakementioning
confidence: 99%